The Stimulus of Physical Activity, Exercise Motives, and Sports Engagements to Improve Sportsman Mental Health: A Quantitative Study on Canadian Universities - Fedak Thompson,; Darchia Maia, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The objective of this study is to examine the associations between physical activity, exercise motivations, sports participation, and mental well-being among university students in Canada. A quantitative research approach was utilised in this study, employing a cross-sectional design and a convenient sampling method. Data were collected from a sample of 500 students enrolled in sports universities. The collected data were then analysed using SPSS software. The study revealed a noteworthy positive correlation between physical activity, exercise motivations, sports involvement, and mental well-being. In particular, there exists a positive association between elevated levels of physical activity (PA), heightened exercise motivations, and increased involvement in sports with improved outcomes in mental health. The results of multiple regression analyses demonstrated that the combination of these three factors accounted for a significant proportion of the variability observed in mental health scores, underscoring their significance in fostering psychological well-being. The results of the study have practical implications for universities in Canada. In order to optimise the welfare of students, educational institutions should give precedence to implementing strategies that foster physical activity within campus premises, facilitate the cultivation of robust exercise motivations, and advocate for active participation in sports. Establishing an atmosphere conducive to mental well-being and comprehensive growth has the potential to enhance the overall academic achievement of students. Additionally, it has been proposed that the research indicators may elicit the release of neurotransmitters such as endorphins and serotonin within the brain, which are known to contribute to an enhanced emotional state. Additionally, it has the potential to enhance one's physical fitness, thereby contributing to an elevated emotional state.